Functional Outcomes And Limb Stability After Single Bone Forearm Reconstruction In Patients With Large Forearm Bone Loss - Singh Rathore, Sawai; Meena, D S; Narayan, Vikrant; Ashok, Ashok (Journal of Neonatal Surgery, 2025)
Background: Large bone defects in the forearm pose significant challenges due to the complex anatomy and essential functions of the upper limb. Single bone forearm reconstruction offers an alternative surgical approach aimed at restoring limb stability and function. This study evaluates the functional outcomes and limb stability in patients undergoing this procedure. Methods: A prospective interventional study was conducted on 30 patients with large forearm bone defects treated with single bone forearm reconstruction at a tertiary care center. Patients were followed for a minimum of 12 months. Functional outcomes were assessed using the Peterson scoring system, grip strength measurements, and range of motion evaluations. Pain levels were measured using the Visual Analog Scale (VAS), and complications were recorded. Results: The majority of patients (83.33%) achieved excellent outcomes according to the Peterson score. Bone union without grafting was achieved in 80% of cases, while 20% required bone grafts. Pronation and supination were limited in 60% of patients fixed in mid-prone position, but wrist function and grip strength were largely preserved. Complications were minimal, with only 6.66% of patients experiencing issues such as volar subluxation of the wrist and skin flap necrosis. Patient satisfaction was high, with 93.33% reporting satisfaction with the surgical outcome. Conclusion: Single bone forearm reconstruction is an effective surgical option for patients with large forearm bone defects, providing excellent functional outcomes and limb stability with minimal complications. This technique should be considered in managing complex forearm injuries where other reconstructive options are limited.